Implementation of the Health Belief Model to Explore Elderly Health Post Service Utilization in Jaten, Karanganyar District, Central Java, Indonesia - Herry Putut Cahyono; Setyo Sri Rahardjo; Bhisma Murti; Revi Gama Hatta Novika; Ika Sumiyarsi Sukamto (Masters Program in Public Health, Sebelas Maret University, 2025)
Background: The utilization of elderly integrated health post (posyandu) visits remains a significant issue affecting the health status of older adults. Elderly health post service serves as a community-based health service platform designed to cater to the needs of the elderly population. However, the utilization of elderly health post service visits is still very low. This study aims to analyze the factors associated with the utilization of elderly health post service services based on the Health Belief Model (HBM). Subjects and Method: The study employed a cross-sectional design and was conducted in Jaten District, Karanganyar, Central Java, Indonesia, from March to April 2025. Sampling was carried out using a multistage sampling method, involving 210 elderly individuals from 30 existing elderly health post service centers. The dependent variable was the utilization of elderly health post service. The independent variables were perceived susceptibility, perceived severity, perceived benefit, perceived barrier, cues to action, and self-efficacy. Data were collected using a questionnaire. Path analysis was employed for data analysis. Results: The utilization of elderly health post service was significantly influenced by perceived susceptibility (b= 0.22; 95% CI= 0.09 to 0.35; p= 0.001), perceived barrier (b= -0.29; 95% CI= 0.42 to -0.15; p <0.001), and self-efficacy (b= 0.13; 95% CI= 0.01 to 0.26; p= 0.038). It was indirectly affected by perceived benefits, perceived susceptibility, perceived severity, and cues to action. Conclusion: The utilization of elderly health post service services is directly influenced by perceived susceptibility, perceived barriers, and self-efficacy. Indirectly, the utilization of elderly health post service visits is affected by perceived barriers, perceived benefits, perceived susceptibility, perceived severity, and cues to action.